The golden compass - Pullman, Philip, 1946- (Pullman, Philip, 1946- His dark materials, 1996)
Accompanied by her daemon, Lyra Belacqua sets out to prevent her best friend and other kidnapped children from becoming the subject of gruesome experiments in the Far North.